COVID as a catalyst: medical student perspectives on professional identity formation during the COVID-19 pandemic - Williams-Yuen, Jordan; Shunmugam, Mahesh; Smith, Haley; Jarvis-Selinger, Sandra; Hubinette, Maria (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2022)
Background: As a result of the COVID-19 pandemic, a national decision was made to remove all medical students from clinical environments resulting in a major disruption to traditional medical education. Our study aimed to explore medical student perspectives of professional identity formation (PIF) during a nationally unique period in which there was no clinical training in medical undergraduate programs.Methods: We interviewed fifteen UBC medical students (years 1-4) regarding their perspectives on PIF and the student role in the setting of the COVID-19 pandemic. Data were analysed iteratively and continuously to create a codebook and identify themes of PIF based on interview transcripts.Results: We identified three key themes: (1) Medical students as learners vs contributing team members (2) Decreased competency as a threat to identity and (3) Doctors as heroes. Conclusions: The impact of disruptions due to COVID-19 catalyzed student reflections on their role within the healthcare system, as well as the role of self-sacrifice in physician identity.  Simultaneously, students worried that disruptions to clinical training would prevent them from actualizing the identities they envisioned for themselves in the future.  Ultimately, our study provides insight into student perspectives during a novel period in medical training, and highlights the unique ways in which PIF can occur in the absence of clinical exposure.